Rancang Bangun Prototype Sistem Monitoring Tandon Otomatis Menggunakan Mikrokontroller ESP32 Berbasis Internet Of Things - Rudi Yanuar; Suryanto Suryanto (Politeknik Kampar, 2023)
Filling reservoir water automatically using a pressure switch and radar is still not effective, because it cannot know how much water is in the reservoir in real time and how much water comes out of the reservoir. In addition, there is a problem with drilled wells where the source of water is not always available, when the well runs out the water pump will run continuously and can cause damage to the water pump. Therefore this study aims to make reservoir water filling automatic, maintain water availability in reservoirs, monitor water in reservoirs in real time, remote control and protect water pumps when well water supplies run out. This research was made using the ESP32 microcontroller, water flow sensor, water switch sensor and also utilizing the HC-SR04 ultrasonic sensor. This research produces a tool that can work well for monitoring how much water is in the reservoir, turning off or on the pump automatically based on the water level in the reservoir, monitoring how much water discharge comes out of the reservoir and monitoring whether or not there is input of water into the reservoir so that the water pump does not lights up continuously when the well or reservoir water runs out to prevent damage to the water pump. All of these systems are controlled by the ESP32 microcontroller which is connected to the internet of things and Android devices so that they can be monitored in real time.